Genotypic and Phenotypic Variability and Heritability of Generative Traits, Yield Components, and The Yield in 39 Cayenne Pepper (Capsicum annuum L.) Genotypes - Almunawar, Said Agil; Herison, Catur; Handajaningsih, Merakati; Alnopri; Romeida, Atra; Rustikawati; Sukisno (Badan Penerbitan Fakultas Pertanian (BPFP), Fakultas Pertanian, Universitas Bengkkulu, 2025)
Cayenne pepper is a horticultural crop with high economic value, and its productivity can be improved through plant breeding programs. Genotypic and phenotypic variability, and heritability are important parameters for such programs. This study aimed of obtaining information on genotypic and phenotypic variability as well as heritability of generative traits, yield components, and the yield in 39 cayenne pepper genotypes. The research was conducted from May to October 2024 at the Experimental Farm, the University of Bengkulu. A Randomized Complete Block Design (RCBD) was used, involving 39 genotypes planted in three replications, with 20 plants per replication. The results showed broad genotypic variability was found in days to anthesis, days to first harvest, number of fruits per plant, fruit diameter, fruit length, pedicel length, and average fruit weight. Broad phenotypic variability was observed in all traits. High heritability was found in days to anthesis, fruit diameter, fruit length, and average fruit weight. These findings are highly valuable for determining effective selection strategies in plant breeding and the development of superior cultivars. Keywords: breeding, chili pepper, diversity, genotypic variance, phenotypic variance.